Impact of the Ukraine-Russia Conflict on the Stability of Energy Geopolitics in Southeast Asia - Prabowo, Tri Bagus; Sihaloho, Rezya Agnesica Helena (Journal of International Relations on Energy Affairs, 2024)
The conflict between Ukraine and Russia holds significant implications for global energy stability, particularly impacting the Southeast Asia region. This conflict has led to a rise in global oil prices, which indirectly affects Southeast Asia. This paper aims to elucidate and analyze how the Ukraine-Russia conflict influences energy stability in Southeast Asian countries. Utilizing a qualitative methodology, this research adopts a descriptive-analytic approach, thereby allowing for a detailed exploration of the conflict's impact on the region's energy stability. Findings reveal that the European Union's longstanding dependence on Russian gas deeply entwines with ASEAN's efforts to leverage energy trade to sustain economic stability, subsequently influencing various derivative sectors. The conflict has undeniably affected the energy supply and demand dynamics, necessitating a shift towards more transparent policies on alternative energy sources. Despite not experiencing direct disruptions in the supply chain or immediate spikes in energy costs, the ripple effects of the conflict have led to an inevitable rise in fuel prices within ASEAN, thus affecting the economic and political landscapes of Southeast Asia.